Evaluasi Kemampuan Siswa SMK NU 1 Karanggeneng dalam Memahami Materi PAI Berbasis Gamifikasi - Nila Rohmania Afwani; Khotimatus Sholikah; Khoirotun Ni’mah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the current digital age, integrating technology into the classroom is essential to producing more engaging and productive learning. Gamification, or the use of gaming aspects into the teaching and learning process, is one of the emerging strategies. The purpose of this study is to ascertain how the Gimkit application is used in Islamic Religious Education (PAI) instruction at SMK NU 1 Karanggeneng, as well as the effects it has on student motivation and comprehension. A descriptive qualitative approach is the methodology employed, and data is gathered by documentation, interviews, and observation. The study's findings demonstrated that the use of Gimkit may produce an engaging, competitive, and dynamic learning environment. Pupils get more motivation, engagement, and comprehension of the subject matter. Despite challenges including a lack of gadgets and internet connection, instructor support and student excitement are crucial to this approach's success. To sum up, gamification using Gimkit is a useful and pertinent learning technique to raise the standard of PAI instruction in the digital age.